The Effectiveness of Spirituality Group Therapy on Happiness and Hardiness in Elderly Women - Esmaeil Sadri Damirchi; Nasim Mohammadi (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective: Spirituality as the basis of beliefs is an important aspect of the life of the elderly and plays a vital role in providing and improving their psychological happiness and hardiness. The purpose of this study was to investigate the effectiveness of spirituality group therapy on happiness and hardiness in elderly women. Method: The research method was semi-experimental with pretest-posttest design with control group. The statistical population of study included all the elderly in Rasht in 2015. Using convenience sampling, 30 of them were selected and randomly assigned to the experimental group (15 participants) and control group (15 participants). The experimental group underwent 10 sessions of spirituality group therapy program which was in line with Richards and Bergin's pattern. The Oxford Happiness Questionnaire and Ahvaz Psychological Hardiness Questionnaire were used for data collection. Data were analyzed using multivariable co-variance test. All ethical issues were observed in the study and the researchers declared no conflict of interests. Results: The findings supported the effectiveness of spirituality group therapy on the elderly's psychological happiness and hardiness. Indeed, the old women in the experimental group scored significantly higher in the happiness and hardiness posttest questionnaires compared to their counterparts in the control group (p<0/01). Conclusion: It can be concluded that spiritual group therapy has a significant impact on seniors' happiness and hardiness. Thus, this method can be useful as a tool for increasing happiness and hardiness of the elderly. For downloading the full-text of this article please click here.